Analysis of the correlation between the group-based trajectory modeling of serum osmolality and prognosis in patients with sepsis-associated encephalopathy at 72 h after admission - Wentao Wu; Chen Wang; Yuhua Zhang; Yongpeng Xie; Xiaomin Li (BMC Infectious Diseases)
Abstract Background This study aimed to identify distinct trajectories of serum osmolality within the first 72 h for patients with sepsis-associated encephalopathy (SAE) in the MIMIC-IV and eICU-CRD databases and assess their impact on mortality and adverse clinical outcomes. Methods In this retrospective cohort study, patients with SAE from the MIMIC-IV database were included. Group-based trajectory modeling (GBTM) was used to categorize distinct patterns of serum osmolality changes over 72 h in ICU patients. Differences in survival across the trajectory groups were compared using Kaplan-Meier (K-M) survival curves. Results A total of 11,376 patients with SAE were included in the analysis, with a median age of 65.6 ± 16.5 years. The in-hospital mortality rate at 30 days was 12.8%. Based on model-defined criteria, three distinct osmolality trajectory groups were identified: Group 1 (59.6%), Group 2 (36.4%), and Group 3 (4.0%). Kaplan-Meier survival analysis indicated that patients with relatively lower serum osmolality within the normal range (Group 1) had a lower 30-day mortality rate compared to those in the other groups (Group 2 and 3). Subgroup analysis demonstrated significant interactions (P < 0.05) between osmolality trajectories and covariates such as the Sequential Organ Failure Assessment (SOFA), vasopressor use and renal replacement therapy (RRT). Conclusion Identifying distinct serum osmolality trajectories may help recognize SAE patient subgroups with varying risks of adverse outcomes, providing clinically meaningful stratification.